PENGARUH PEMBERIAN BERBAGAI KONSENTRASI KOLKHISIN TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN CABAI (CAPSICUM ANNUM) VARIETAS LADO F1 - Syaifudin, Achmad; Ratnasari, Evie; Isnawati, Isnawati (LenteraBio: Berkala Ilmiah Biologi, 2013)
Pepper production in Indonesia is still very low. One effort that can be done is by using the plant breeding colchicine. Colchicine is one of the reagents for the mutation that causes polyploid, the organism has three or more sets of chromosomes in polyploid cells. The purpose of this study were to describe differences in growth and productivity in pepper (Capsicum annuum) caused by immersion in a solution colchicine sprouts at various concentrations and to determine the concentration of the most optimal colchicine?s solution influence on the growth and productivity of pepper plants as the risk of ploidisasi. The research was carried out experimentally using a randomized block design with one treatment factor is the concentration of a solution that includes 5 colchicine concentrations, ie 0 ppm (K1), 5 ppm (K2), 10 ppm (K3), 15 ppm (K4), and 20 ppm (K5). The treatment was repeated 5 times to obtain 25 units and placement experiments performed randomly in each block. Data includes pepper plant height, pepper plant biomass, pepper fruit number and papper fruit biomass statistically tested by one-way ANOVA test and if the result is significant continued using Duncan's test. The results obtained showed that the treatment of various concentrations colchicine on soaking sprouts make a difference on the growth and yield of pepper. Concentration of 15 ppm kolkhisin give optimal results on the growth and yield of pepper.